Factors affecting the Implementation of Strategic plan in Health Care: A casa Study of Machakos County Hospitals - Nzuki, Hellen N. (My University, 2017)
Strategic planning and its implementation in Kenya at the Ministry of Health is an element of the on-going public sector reforms designed to improve the delivery of health care services. However, this implementation has been facing different challenges. This study sought to investigate these challenges with specific reference to hospitals in Machakos County. The objectives include: To assess how strategic plan awareness affects strategic plan implementation at Machakos County public hospitals; to assess the effect of human resource staffing norms in strategic plan implementation at Machakos County public hospitals and to determine the extent to which organization structure affect strategic plan implementation at Machakos County public hospitals. The study employed a correlation research design in assessing the effect of various challenges on implementation of health sector strategic plans in Kenya. The target population comprised of officers at different management levels in Machakos County public hospitals. Stratified random sampling was adopted were all officers with personal identification number based on different strata had an equal opportunity of taking part in the study. Major strata which were considered included doctors, clinical officers, nurses and support staff. Data was collected using a semi-structured questionnaire that included open-ended questions as well as closedended questions. The collected data was analyzed using descriptive and inferential statistics. The study findings revealed that staff awareness; human resource staffing norms and organizational structure have a significant effect on the implementation of strategic plans of hospitals in Machakos County. For purpose of policy, the study recommends that, hospitals should be managed in such a way that there will be adequate advocacy in relation to strategic planning so as to meet their objectives. Such strategies will create awareness among staff members making them part of the process of implementing the strategic plan. All stakeholders should be engaged in the implementation of strategic plans aimed at reducing resistance from the stakeholders in the process of strategy implementation. The management should therefore ensure that employees with relevant specialties are employed to attend to patients and oversee strategy implementation to enable the hospitals attain their objectives. Hospital management should ensure that there is smooth flow of information pertaining strategy implementation. This will ensure that there is no communication breakdown which hinders implementation of strategic plans. Sufficient resources should be allocated to ensure set strategies and activities are implemented. This coupled with proper coordination and monitoring and evaluation will go a long way in implementing strategic plans in the health sector.
Keywords: Strategic planning